2021
DOI: 10.4054/demres.2021.45.43
|View full text |Cite
|
Sign up to set email alerts
|

Gender division of housework during the COVID-19 pandemic: Temporary shocks or durable change?

Abstract: BACKGROUNDFirst evidence shows that lockdown and confinement measures were associated with a more egalitarian gender division of housework in the United Kingdom. However, we know little about how the gender division of housework adjusted in different phases of the pandemic. OBJECTIVEWe ask: (1) How did the gender division of housework change with the first national lockdown in March 2020? (2) Did observed changes persist when the lockdown measures were lifted or did couples revert to the gender division of hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Although some couples had more time on their hands, parents may have had to unexpectedly homeschool and care for children who were unable to attend school or childcare. The homeschooling burden disproportionately fell on mothers, as couples often reverted to traditional gender roles (Benzeval et al, 2020; Sánchez et al, 2021). In addition, women were more likely to reduce work hours, withdraw from the labor market or apply for furlough (Adams‐Prassl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although some couples had more time on their hands, parents may have had to unexpectedly homeschool and care for children who were unable to attend school or childcare. The homeschooling burden disproportionately fell on mothers, as couples often reverted to traditional gender roles (Benzeval et al, 2020; Sánchez et al, 2021). In addition, women were more likely to reduce work hours, withdraw from the labor market or apply for furlough (Adams‐Prassl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the mental health disadvantages of women during the lockdown may be linked to the clear gender inequalities in paid work, housework, and care work, all of which were strongly affected by the measures the government imposed to tackle the COVID-19 pandemic. The existing evidence on the consequences of the COVID-19 lockdown suggests that while men increased their overall contributions to housework and care work from low initial levels, the lockdown was not the great equalizer but, rather, reaffirmed or even magnified the existing gender inequalities within couples with children (Czymara, Langenkamp, and Cano 2021; Hank and Steinbach 2020; Kreyenfeld and Zinn 2021; Möhring et al 2020; Rodríguez Sánchez, Fasang, and Harkness 2021). Therefore, it is likely that after the onset of the pandemic, women’s unpaid workload further increased from already high levels because during the spring lockdown, families were spending more time at home than they were before the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…There are good reasons to assume that the mental health disadvantage of mothers increased over the course of the pandemic in light of the results emerging from data on an early phase of the pandemic. Research on the division of housework during the pandemic has already shown that even among couples who shared housework more equally during the early months of the pandemic, this increase in gender equality had vanished a few months later, particularly for couples with children (Rodríguez Sánchez, Fasang, & Harkness, 2021). This was also the case for couples who shared care work more equally during the pandemic.…”
Section: Discussionmentioning
confidence: 99%